2017
DOI: 10.20471/acc.2017.56.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect – Comparison of Paracetamol Administered Intermittently and Through Patient-Controlled Analgesia Pump after Lumbar Discectomy: a Prospective Clinical Study

Abstract: SUMMARY -Lumbar discectomy is the most common surgical treatment for intervertebral disc extrusion. Postoperative pain is a common clinical problem that greatly aff ects the length of hospitalization, functional status and patient quality of life. Th e aim of this study was to compare the postoperative analgesic effi cacy of paracetamol administered intermittently and through patient-controlled analgesia (PCA) pump following single level lumbar discectomy. Patients who underwent elective lumbar discectomy of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Postoperative pain relief was the third most common primary outcome of interest (n=13, 15% of included studies), 22 , 24 , 31 , 34 , 36 , 41 , 50 , 51 , 55 , 62 , 65 , 72 , 92 and a secondary outcome in 13 studies (15%). 35 , 40 , 47 , 52 , 60 , 69 , 75 , 76 , 79 , 81 , 86 , 87 Interventions of interest in the studies where pain was the primary outcome included hypnosis; 55 anaesthetic technique (for hysteroscopy); 51 play; 72 Reiki; 34 premedication and information; 50 different routes of paracetamol administration; 41 , 62 cold application; 65 guided imagery and relaxation; 22 positioning and early sandbag removal (post-coronary angiography); 92 room air versus carbon dioxide (CO 2 ) insufflation; 24 , 31 and bed positioning. 36 Nine studies had adult participants, 31 , 34 , 36 , 41 , 50 , 51 , 62 , 65 , 92 two were pediatric based, 55 , 72 and one study focused on adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperative pain relief was the third most common primary outcome of interest (n=13, 15% of included studies), 22 , 24 , 31 , 34 , 36 , 41 , 50 , 51 , 55 , 62 , 65 , 72 , 92 and a secondary outcome in 13 studies (15%). 35 , 40 , 47 , 52 , 60 , 69 , 75 , 76 , 79 , 81 , 86 , 87 Interventions of interest in the studies where pain was the primary outcome included hypnosis; 55 anaesthetic technique (for hysteroscopy); 51 play; 72 Reiki; 34 premedication and information; 50 different routes of paracetamol administration; 41 , 62 cold application; 65 guided imagery and relaxation; 22 positioning and early sandbag removal (post-coronary angiography); 92 room air versus carbon dioxide (CO 2 ) insufflation; 24 , 31 and bed positioning. 36 Nine studies had adult participants, 31 , 34 , 36 , 41 , 50 , 51 , 62 , 65 , 92 two were pediatric based, 55 , 72 and one study focused on adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…107 Two studies focused on adolescents, 22 , 37 and one study included both adults and children. 84 Although older adults (>75 years) were included in some studies 52 , 60 , 62 they were not specifically identified as the target population in any of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the performance of more well-conducted RCTs comparing different times of IV paracetamol used on postoperative analgesia is needed. Kurtovic et al (2017) compared the postoperative analgesic efficacy of intravenous paracetamol administered intermittently and through a patient-controlled analgesia (PCA) pump following lumbar discectomy. They found an interesting result, that patients in both groups had satisfactory pain control results.…”
Section: Discussionmentioning
confidence: 99%
“…Acetaminophen and NSAIDs are recommended as the rst-line medication options for most patients with low back pain (grade 1A evidence) in 2007 by the Diagnosis and treatment of low back pain: a joint clinical practice guideline from the American College of Physicians and the American Pain Society [ 6] . The e cacy of acetaminophen in the treatment of LDH has also been reported [ 7] , but it can only relieve pain and has no effect on other symptoms of LDH. However, acupuncture, massage and other complementary therapies have been widely used in the treatment of lumbar disc herniation [ 8] .…”
Section: Introductionmentioning
confidence: 93%